The longitudinal health economic impact of viral encephalitis in the United States. Issue 2 (10th February 2020) - Kiyani, Musa; Liu, Beiyu; Charalambous, Lefko T.; Adil, Syed M.; Hodges, Sarah E.; Yang, Siyun; Pagadala, Promila; Perfect, John R.; Lad, Shivanand P.
Abstract : Introduction. Previous studies of viral encephalitis have focused on acute costs, estimating incidence at 7.3 per 100 000 and total US annual charges at 2 billion in 2010. Aim. We aim to quantify the most updated longitudinal health economic impact of viral encephalitis in the USA from 2008 to 2015. Methodology. Data on patients diagnosed with viral encephalitis were obtained from the Truven Health Analytics MarketScan database. Patients with a primary diagnosis of viral encephalitis, from herpetic viruses and other viral aetiologies (e.g. West Nile fever) were included in the analysis. Data concerning healthcare resource utilization, inpatient mortality, length of stay and accrued healthcare costs were collected for up to 5 years. Results. Among 3985 patients with continuous enrolment for 13 months prior to the encephalitis diagnosis, more non-herpes simplex encephalitis (61.7 %) than herpes simplex encephalitis (HSE; 38.3 %) cases were recorded, with the majority concentrated in the southern USA (29.2 %). One-year inpatient mortality was 6.2 %, which over a 5-year period rose to 8.9 % for HSE and 5.8 % for all other viral encephalitides. HSE resulted in longer cumulative stays in the hospital (11 days vs. 4 days; P =0.0025), and accrued 37 % higher first-year costs, after adjusting for known confounders [ P <0.001, cost ratio=1.37, 95 % confidence interval (1.20, 1.57)]. Additionally, HSE was associated with greater 5-year cumulative median charges (125 338 vs. 82 317, P =0.0015). Conclusion. The health economic impact and long-term morbidity of viral encephalitis in the USA are substantial.